2018
DOI: 10.2106/jbjs.18.00079
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Sustainability of a Standardized Care Pathway Developed with Use of Lean Process Mapping for the Treatment of Patients Undergoing Posterior Spinal Fusion for Adolescent Idiopathic Scoliosis

Abstract: Background: Recent changes in health care have begun to shift the industry from a volume-based to a value-based focus. This shift has led to standardized care pathways that decrease care variability, improve outcomes, and decrease cost. Although numerous studies have described standardized pathways for adolescent idiopathic scoliosis (AIS), few have demonstrated sustainability. We report the effectiveness and sustainability of a standardized care pathway for patients undergoing posterior spinal fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 23 publications
0
27
1
Order By: Relevance
“…ERAS has a positive financial impact on the utilization of health care resources [ 27 ]. There are many factors that contribute to the overall cost of PSF in AIS patient with charges often exceeding $100,000 [ 8 , 20 ]. Fletcher et al[ 13 ] showed that when compared to traditional protocols, the use of ERAS protocols resulted in a 33% reduction in room charges ($1,885 ± 486 vs. $2,779 ± 617, p < 0.0001) and an 11% reduction in therapy charges ($554 ± 201 vs. $619 ± 219, p = 0.004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERAS has a positive financial impact on the utilization of health care resources [ 27 ]. There are many factors that contribute to the overall cost of PSF in AIS patient with charges often exceeding $100,000 [ 8 , 20 ]. Fletcher et al[ 13 ] showed that when compared to traditional protocols, the use of ERAS protocols resulted in a 33% reduction in room charges ($1,885 ± 486 vs. $2,779 ± 617, p < 0.0001) and an 11% reduction in therapy charges ($554 ± 201 vs. $619 ± 219, p = 0.004).…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the surgical time it was suggested to limit the fluoroscopy checks for verifying the placement of pedicle screws, but this of course needs to be balanced against patient safety [ 19 ]. It was also suggested to use power tools for placing the pedicle screws to reduce the surgical time [ 20 ]. Use of intra-thecal morphine injections (5 μg/kg up to 250 μg) along with subcutaneous bupivacaine wound infiltration at the end of surgery was utilized to enhance post-operative analgesia [ 15 , 18 , 19 ].…”
Section: Intraoperative Protocolmentioning
confidence: 99%
“…Four projects [75][76][77][78] reported both "as-is" and "to-be" maps, while 5 describe the "to-be" process. [79][80][81][82][83] For example, in TDABC projects the analysis is focused on process costs and is mainly completed after the "as-is" process map is created. [84][85][86][87][88][89] In projects implementing evidence-based recommendations, a process analysis was completed before the creation of the ideal or "to-be" process map.…”
Section: Phasementioning
confidence: 99%
“…[84][85][86][87][88][89] In projects implementing evidence-based recommendations, a process analysis was completed before the creation of the ideal or "to-be" process map. [83] Most studies (78%) reported that additional information gathered during the PM exercise-such as delays, safety problems, or ow of information, resources and activity -is represented on the nal map. Only 48% of studies speci ed that the PM exercise had been reviewed for accuracy and con rmed by key stakeholders or external experts.…”
Section: Phasementioning
confidence: 99%
See 1 more Smart Citation